Extrusion of PHA-containing bacterial biomass and the fate of endotoxins: A cost-reducing platform for applications in molding, coating and 3D printing. (December 2022) - Collet, Christophe; Vaidya, Alankar A.; Gaugler, Marc; West, Mark; Lloyd-Jones, Gareth
Abstract: Manufacturing polyhydroxyalkanoate (PHA) polymers is expensive compared to oil-based plastic with as much as 50% of the cost attributed to purification. We have processed PHA-containing bacterial biomass directly by extrusion to avoid purification steps to produce new biocomposites for applications in moulding, coating and 3D printing. Direct incorporation of PHA-containing bacteria into biocomposites provides two significant advantages for cost reduction, firstly by avoiding PHA purification, and secondly by incorporating biomass as a low-cost sustainable filler in the new materials. Three key steps were required: firstly biomass containing > 50% by weight of PHA was prepared for three different PHAs (PHB, PHBV and mcl-PHA) so as to avoid the need to add extra purified PHA as previously reported; extruded biocomposites were prepared to analyse the fate of whole cells and ensure that the properties of the PHA were maintained and the impact of the biomass filler assessed; and thirdly that the bioavailability of bacterial endotoxins (pyrogens) which are present at very high levels in many PHA-producing bacterial strains was assessed and shown to be significantly reduced during extrusion to levels similar to commercially-produced purified PHB. These three steps have opened a route to whole-cell PHA-based biocomposites that will be less expensive to produce compared to purified PHA. The identification of an endotoxin-free Gram-negative production host enhances the suitability of sphingomonads as a new endotoxin-free PHA production platform. Graphical Abstract: ga1 Highlights: Direct processing of PHA-containing biomass by extrusion without prior PHA recovery. Desired properties of each PHA retained after whole cell processing. Applications in molding, coating and 3D printing. The bioavailability of bacterial endotoxins decreased significantly during extrusion. Elementally balanced (C:N:P:S) to enhance decomposition and composting of PHA biocomposites.